Introduction to the Special Issue "The 2015 Swiss National Elections". Issue 4 (10th December 2018) - Giger, Nathalie; Rennwald, Line; Tresch, Anke
Abstract: This special issue brings together a large variety of contributions dealing with party choice, political attitudes and the dynamics of electoral campaigns in Switzerland. The introduction places the contributions in the broader framework of current debates in the international literature and highlights substantial and methodological innovations. The articles in this volume address central issues of the literature dealing with the two‐dimensional structure of political competition, take up key questions of the dynamics of election campaigns, and finally echo a large interest for the topic of populism, not only on the side of the parties but also on the side of the voters. The introduction also underlines the new and innovative ways in which the articles link the different datasets together in order to address substantial questions on the complexity of the environment in which voters form their choice and political parties operate during an election campaign.